From multiculturalism to integration: the role of Muslim women in the implementation of ethno-religious minority policies in the UK (2001-2014) - Qureshi, Abeeda (2016)
This thesis examines the role of Muslim women in the implementation of ethno-religious minority policies in the UK from 2001-2014. Using Muslim women as a case study, I aim to understand how this relationship works in practice and whether the role played by Muslim women is symbolic or substantive. Also, I attempt to explore whether the engagement between the government and Muslim women has increased since 2010, with the change in the government from New Labour to the Coalition. Last but not least, the representative claims of the women involved in the policy process is examined to determine the legitimacy of the whole process.